The protein kinase C super‐family member PKN is regulated by mTOR and influences differentiation during prostate cancer progression. Issue 15 (6th September 2017) - Yang, Chun‐Song; Melhuish, Tiffany A.; Spencer, Adam; Ni, Li; Hao, Yi; Jividen, Kasey; Harris, Thurl E.; Snow, Chelsi; Frierson, Henry F.; Wotton, David; Paschal, Bryce M.
Abstract : Background: Phosphoinositide‐3 (PI‐3) kinase signaling has a pervasive role in cancer. One of the key effectors of PI‐3 kinase signaling is AKT, a kinase that promotes growth and survival in a variety of cancers. Genetically engineered mouse models of prostate cancer have shown that AKT signaling is sufficient to induce prostatic epithelial neoplasia (PIN), but insufficient for progression to adenocarcinoma. This contrasts with the phenotype of mice with prostate‐specific deletion of Pten, where excessive PI‐3 kinase signaling induces both PIN and locally invasive carcinoma. We reasoned that additional PI‐3 kinase effector kinases promote prostate cancer progression via activities that provide biological complementarity to AKT. We focused on the PKN kinase family members, which undergo activation in response to PI‐3 kinase signaling, show expression changes in prostate cancer, and contribute to cell motility pathways in cancer cells. Methods: PKN kinase activity was measured by incorporation of 32 P into protein substrates. Phosphorylation of the turn‐motif (TM) in PKN proteins by mTOR was analyzed using the TORC2‐specific inhibitor torin and a PKN1 phospho‐TM‐specific antibody. Amino acid substitutions in the TM of PKN were engineered and assayed for effects on kinase activity. Cell motility‐related functions and PKN localization was analyzed by depletion approaches and immunofluorescence microscopy, respectively. The contribution of PKN proteins to prostate tumorigenesis was characterized in several mouse models that express PKN transgenes. The requirement for PKN activity in prostate cancer initiated by loss of phosphatase and tensin homolog deleted on chromosome 10 (Pten), and the potential redundancy between PKN isoforms, was analyzed by prostate‐specific deletion of Pkn1, Pkn2, and Pten. Results and Conclusions: PKN1 and PKN2 contribute to motility pathways in human prostate cancer cells. PKN1 and PKN2 kinase activity is regulated by TORC2‐dependent phosphorylation of the TM, which together with published data indicates that PKN proteins receive multiple PI‐3 kinase‐dependent inputs. Transgenic expression of active AKT and PKN1 is not sufficient for progression beyond PIN. Moreover, Pkn1 is not required for tumorigenesis initiated by loss of Pten. Triple knockout of Pten, Pkn1, and Pkn2 in mouse prostate results in squamous cell carcinoma, an uncommon but therapy‐resistant form of prostate cancer.